Phenotypic characterization of stem cell factor-dependent human foetal liver-derived mast cells. - Nilsson, G (1993)
Human foetal liver cells are an enriched source of mast cell progenitors that complete their differentiation and mature in response to stem cell factor, the ligand for Kit, in liquid culture. These mast cells are Kit+, metachromatic with toluidine blue+, tryptase+, histamine+ and show ultrastructure features of mast cells. Using a panel of monoclonal antibodies (mAb) against different cell-surface antigens (33 mAb were used), the cell-surface phenotype of human stem cell factor-dependent foetal liver-derived mast cells was examined by flow cytometry. Consistent with previous reports on tissue-derived mast cells, those derived from foetal liver in vitro expressed HLA class I, CD9, CD29, CD33, CD43, CD45 and Kit. Unlike mast cells dispersed from tissue, a high expression of CD13 was found. Also, these in vitro-derived mast cells express little, if any, high-affinity IgE receptor. However, small amounts of mRNA for the alpha-chain in foetal liver-derived mast cells compared to KU812 cells (a human basophil-like cell line) could be detected by Northern blotting. Full expression of Fc epsilon RI may require additional growth factor(s).